2019
DOI: 10.1128/jvi.01861-18
|View full text |Cite
|
Sign up to set email alerts
|

Packaging of the Influenza Virus Genome Is Governed by a Plastic Network of RNA- and Nucleoprotein-Mediated Interactions

Abstract: The genome of influenza A virus is organized into eight ribonucleoproteins, each composed of a distinct RNA segment bound by the viral polymerase and oligomeric viral nucleoprotein. Packaging sequences unique to each RNA segment together with specific nucleoprotein amino acids are thought to ensure the precise incorporation of these eight ribonucleoproteins into single virus particles, and yet the underlying interaction network remains largely unexplored. We show here that the genome packaging mechanism of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…argues against a strict, non-variable sequence of vRNP interactions consistent with recent experimental and modelling reports 14,37,38 . In the latter case, we would have expected a single distinct MSC composition to stand out per MSC rank.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…argues against a strict, non-variable sequence of vRNP interactions consistent with recent experimental and modelling reports 14,37,38 . In the latter case, we would have expected a single distinct MSC composition to stand out per MSC rank.…”
Section: Resultssupporting
confidence: 81%
“…Nakatsu et al 39 applied scanning electron microscopy tomography to diverse influenza A and B strains and showed that at least 80% and in some cases even 100% of virions contained a complete genome arranged in the '7 + 1' pattern. Reverse genetics approaches have shown that deletions or mutations in a packaging signal sequence of a single vRNA can prevent the incorporation of other vRNPs into virions or virus-like particles 2,14,40 . Very likely, the dense arrangement of vRNPs in high-rank MSCs forms a surface favouring recognition and preferential incorporation of such complexes into assembling viruses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These comprise for example the co-selection of genome packaging signals in conjunction with a specific set (code) of amino acids in the viral nucleoprotein (NP) [19][20][21]. Both the segmentspecific packaging signals and a compatible NP amino acid code are compulsory to orchestrate the incorporation of the viral genome into progeny virions [22]. Therefore, because of nonmatching packaging sequences and a different NP amino acid code, New World bat and conventional non-bat IAVs are unable to reassort their genomes [20]-an additional unique feature of New World bat IAVs, making them a truly divergent entity of IAVs.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Consistent with this idea, mutations in the conserved RNA terminal regions cause defects in genome packaging [12]- [16]. Genomic RNA strands are seen to physically bind in vitro and in vivo [17]- [19] via RNA base-pairing interactions [20]- [22] and interactions mediated by vRNP-associated proteins [23]- [25]. In addition to the equilibrium RNA-RNA binding measured in vitro, livecell imaging reveals that some inter-segment interactions are irreversible on the timescale of an infection [26].…”
mentioning
confidence: 83%